2001
DOI: 10.1034/j.1399-3046.2001.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias after pediatric lung transplantation

Abstract: Atrial arrhythmias have been reported after congenital heart surgery involving extensive atrial suture lines. Experimental studies involving bilateral lung transplantation (Tx) suggest that the left atrial suture lines predispose to atrial flutter. The overall incidence and type of arrhythmias after pediatric lung Tx have not previously been described and therefore the purpose of this study was to prospectively screen and describe arrhythmias in a subset of our lung transplant population. Over a 1-yr study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Inflammation has been associated with AF, and a higher inflammatory state after surgery may explain the higher incidence of AF early but not late in our cohort. 7,21 AF, AFL, and AT have been described after thoracic surgery and after LT. 2,20,[22][23][24][25] Left AFL has also been described after LT in the pediatric population and after orthotopic heart transplantation. 25,26 The donor PV-left atrial cuff anastomosis with the recipient LA results in putative lines of conduction block that serve as potential substrate for macroreentrant tachyarrhythmia while possibly also compartmentalizing the LA to reduce the incidence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation has been associated with AF, and a higher inflammatory state after surgery may explain the higher incidence of AF early but not late in our cohort. 7,21 AF, AFL, and AT have been described after thoracic surgery and after LT. 2,20,[22][23][24][25] Left AFL has also been described after LT in the pediatric population and after orthotopic heart transplantation. 25,26 The donor PV-left atrial cuff anastomosis with the recipient LA results in putative lines of conduction block that serve as potential substrate for macroreentrant tachyarrhythmia while possibly also compartmentalizing the LA to reduce the incidence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of arrhythmias following pediatric lung transplant patients are sparse and show mixed results. Gandhi et al found an 11% incidence of atrial flutter following lung transplantations, whereas Hoffman et al reported an arrhythmia risk of <5% in a small cohort of patients 13,14 . Given the lack of data, we set out to evaluate our lung transplant patients with a specific focus on the impact of AAs.…”
Section: Discussionmentioning
confidence: 99%
“…Within the pediatric lung transplant population, there is a paucity of data on the development of AAs. In the limited data that do exist, some have concluded that the prevalence and significance is low, while others have seen arrhythmias with some routine 13,14 . At our local institution, we noted that AAs following lung transplant was not uncommon and thus sought to evaluate this patient population further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of commonly recognized postoperative complications in adults after LTx is atrial arrhythmias with reported prevalence up to 50%, leading to increased length of hospital stay and mortality (8)(9)(10)(11)(12)(13). Compared to adults, published data on atrial arrhythmias among children and young adults following LTx are sparse with reported prevalence rates of 11%-20% across pediatric LTx centers (14)(15)(16). Given the changing pediatric LTx landscape, optimization of clinical management of pediatric LTx recipients is a priority, especially in the post-operative time period until discharge (17,18).…”
Section: Introductionmentioning
confidence: 99%